Diversity of Gyrinops versteegii from several agarwood plantation on Lombok Island (Indonesia) as raw material of Gyrinops tea - I GDE ADI SURYAWAN WANGIYANA; SUPRIADI SUPRIADI; ALUH NIKMATULLAH; SUNARPI SUNARPI; AGUNG AYU HARI TRIANDINI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Wangiyana IGAS, Supriadi, Nikmatullah A, Sunarpi, Triandini IGAAH. 2021. Diversity of Gyrinops versteegii from several agarwood plantation on Lombok Island (Indonesia) as raw material of Gyrinops tea. Biodiversitas 23: 178-186. The purpose of this research is to examine the diversity of Gyrinops versteegii as a raw material of agarwood Gyrinops tea based on morphology, phytochemical, and molecular characters. G. versteegii samples were taken from 5 agarwood plantation on Lombok Island: Lingsar, Rarung, Mataram, Kekait, and Pejaring. Variation of G. versteegii stem, leaves, and fruit was the morphology character observed in this study. Qualitative phytochemical screening, quantitative tannin concentration, and the hedonic score of Gyrinops tea were the essential phytochemical character in this study. DNA fingerprinting and RAPD analysis were the molecular characters of this study. All of those characters were used in numeric-phenetics analysis to construct a dendrogram. MVSP program with UPGMA algorithm as clustering method and Simple Matching Coefficient for similarity analysis was used to construct dendrogram. The result has shown variation topology of dendrogram based on morphology, phytochemical, molecular, and combination character. However, all dendrograms had the same number of clusters and cluster members. G. versteegii kekait and G. versteegii Pejaring were grouped to cluster 1 while G. versteegii Rarung and G. versteegii Mataram were grouped to cluster 2. G. versteegii Lingsar was grouped later on the node after cluster 1 or 2. It could be concluded that G. versteegii from Lombok Island Plantation could be divided into three different cluster groups based on the variation of morphology, chemical, and molecular characters.